2017
DOI: 10.1155/2017/5470731
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Endocrine Disorders in Central Ghana

Abstract: Background. Although an increasing burden of endocrine disorders is recorded worldwide, the greatest increase is occurring in developing countries. However, the spectrum of these disorders is not well described in most developing countries. Objective. The objective of this study was to profile the frequency of endocrine disorders and their basic demographic characteristics in an endocrine outpatient clinic in Kumasi, central Ghana. Methods. A retrospective review was conducted on endocrine disorders seen over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
(31 reference statements)
2
9
1
Order By: Relevance
“…Recent hospital based studies from Ghana show that contrary to earlier reports, Graves' disease is not uncommon, comprising 54% of all cases of thyroid dysfunction 44 although there may be ascertainment bias. While this may be due to improvements in iodine nutrition subsequent studies in the aftermath of iodisation in Ghana has shown marked increases in the incidence of both Graves' disease and nodular disease suggesting a role for improved diagnosis 45 .…”
Section: Global Variation In the Epidemiology Of Hyperthyroidism (Figcontrasting
confidence: 61%
“…Recent hospital based studies from Ghana show that contrary to earlier reports, Graves' disease is not uncommon, comprising 54% of all cases of thyroid dysfunction 44 although there may be ascertainment bias. While this may be due to improvements in iodine nutrition subsequent studies in the aftermath of iodisation in Ghana has shown marked increases in the incidence of both Graves' disease and nodular disease suggesting a role for improved diagnosis 45 .…”
Section: Global Variation In the Epidemiology Of Hyperthyroidism (Figcontrasting
confidence: 61%
“…In this 3-year analysis of endocrine consultations at our endocrine clinic, DM, thyroid disorders followed by metabolic syndrome, and HPOs accounted for the highest reasons for endocrine consultations. This is similar to global reports of DM followed by thyroid disorders as the commonest causes of endocrinopathy worldwide 34…”
Section: Discussionsupporting
confidence: 89%
“…According to the World Health Organization data published in 2017, Nigeria is the 10 th country with the highest endocrine-associated mortality worldwide with mortality put at nearly 42,961 (2.11%),2 death rate is 19.56/100,000 deaths, while about 118 people die of endocrine disorders each day, an average of 1 death every 13 min 2. Factors contributing to high endocrine mortality include limited number of endocrinologists, missed or delayed diagnosis by nonspecialists, and priority given to infectious (communicable) diseases 34…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Sarfo-Kantanka et al have reported that thyroid disorders are the second leading cause of endocrine morbidity in central Ghana with hyperthyroidism accounting for 9.2% of all cases seen in their endocrine service. 3 The same authors have reported that toxic multinodular disease is more common than thyrotoxicosis from diffuse goitre in Ghana. 4 In this paper, we aim to highlight the essential role of thyroid scintigraphy in the management of benign thyroid disease and alert clinicians in Ghana to the availability of this resource.…”
Section: Introductionmentioning
confidence: 96%